Apolipoprotein E Mutation and Double Filtration Plasmapheresis Therapy on a New Chinese Patient with Lipoprotein Glomerulopathy - Wencheng Li; Yang Wang; Zhiwu Han; Changqing Luo; Chun Zhang; Jing Xiong (Karger Publishers, 2014)
Background/Aims: Lipoprotein glomerulopathy (LPG) is a rare hereditary disease. In this study, we investigated the apoE mutation and the role of double filtration plasmapheresis therapy (DFPP) on a new Chinese patient with LPG. Methods: Renal biopsy was performed on this patient to allow a definitive diagnosis. The mutations in the coding sequence of apoE and the hereditary pedigree of this patient were investigated by DNA sequencing. The patient was treated with DFPP, and clinical parameters before and after DFPP were compared. Results: Two missense mutations were found in this patient: Cys112Arg and Arg25Cys. Arg25Cys was previously designated as APOE Kyoto. Family genotyping showed that Cys112Arg and Arg25Cys mutation were transmitted through his father and his mother, respectively. The patient's parents are healthy so far to date. Possibly there was a dose effect on apoE mutation induced LPG. Furthermore, DFPP treatment was first used on this patient and led to dramatic changes: Proteinuria and apo E values declined, and hemoglobin level increased significantly. Conclusion: APOE Kyoto mutation was found in a new Chinese patient with LPG, accompanied by Cys112Arg. More cases and further functional experiments are needed to investigate the role of these two mutations together in LPG. DFPP is an effective therapeutic modality for improving NS in patients with LPG.